The Relationship between Body Mass Index and Incident Diabetes Mellitus in Chinese Aged Population: A Cohort Study - M. L. Tang; Y. Q. Zhou; A. Q. Song; J. L. Wang; Y. P. Wan; R. Y. Xu (Journal of Diabetes Research)
Objectives. Previous studies reported that overweight older adults had a lower mortality after cardiovascular diseases attack, indicating being thinner might not always be better. However, there is an ongoing debate about what is the optimal range of body mass index (BMI) for the aged population. We aimed to evaluate the value of BMI for the prediction of incident diabetes mellitus (DM) in the Chinese elderly population. Methods. A total number of 6,911 Chinese elderly people (4,110 men and 2,801 women, aged 71±6.0 years) were included in this cohort study. BMI was measured at baseline (Jan 1, 2014, to Dec 31, 2014). All the participants were further classified into six groups: <18.5 kg/m2, 18.5 to <22.5 kg/m2, 22.5 to <25.0 kg/m2, 25.0 to <27.5 kg/m2, 27.5 to <30.0 kg/m2, and ≥30.0 kg/m2. Fasting blood glucose (FBG) and glycated hemoglobin A1c (HbA1c) were annually measured during follow-up (Jan 1, 2015-May 31, 2019). DM was confirmed if either FBG≥7.0 mmol/L or HbA1c≥6.5%. We used the Cox proportional hazard regression model to evaluate the association between BMI and the prediction of incident DM. Results. Comparing individuals with a BMI range of 18.5 to <22.5 kg/m2 (reference), the hazard ratio for incident DM was 2.13 (95% CI: 1.54~2.95), 2.14 (95% CI: 1.53~3.00), 3.17 (95% CI: 2.19~4.59), 3.15 (95% CI: 1.94~5.09), and 3.14 (95% CI: 1.94~5.09) for the group with a BMI range of 22.5 to <25.0 kg/m2, 25.0 to <27.5 kg/m2, 27.5 to <30.0 kg/m2, and ≥30.0 kg/m2 after adjusting for baseline age, sex, blood pressure, lipid profiles, and eGFR (P trend < 0.001), after adjusting for the abovementioned confounders. The association tended to be closer in men and young participants, compared with their counterparts. Conclusions. High BMI was associated with a high risk of developing DM in the Chinese aged population. Thus, it is optimal for the aged population to maintain their body weight within a reasonable range to prevent chronic diseases.